Bandwidth Management in Routers for DHCP Protocol: Reviewing the Best - Imam, Md. Abdullah Yusuf; Biswas, Prodip Kumar (Science and Technology: Developments and Applications Vol. 9, 2025)
The terms "Bandwidth" and "Data rate" are frequently used interchangeably in the field of telecommunications, which can make things somewhat unclear at times. Bandwidth Management with Static IP is much easier than the DHCP Protocol. Without a Wi-Fi router, in DHCP, the IP changes when the main system (Router) is powered on every time, and the Bandwidth associated with the previous IP also changes. This paper describes the problems and techniques of the previously described two papers and has tried to solve the Bandwidth distribution process during the system's operation in DHCP. It has been found that though Routers operate on IPs, it seems logical, but costly and experimentally very hard to implement, and Bandwidth management for the DHCP Protocol needs a manageable Switch for binding MAC addresses with Bandwidth segments of each device on its ports. In conclusion, DHCP protocol has much more difficulty with IP conflict issues, but also has the advantage also in adding devices without giving it an IP. Bandwidth management in static Routers and in static switches is much easier than DHCP.